Comparative Analysis of The High School Double Track Program and Vocational Education: Implications for Graduates' Work Readiness - Karina Permatasari; Rokhmawati, Isnaini; Yayuk, Erna (Universitas Negeri Semarang, 2024)
This study examines the effectiveness of Indonesia's Double Track Program in Senior High Schools and Vocational Education in enhancing graduates' work readiness. Vocational High Schools (SMK) focus on industry-based technical skills, while the Double Track Program offers additional skills for students not pursuing higher education. Using a qualitative comparative case study at SMA Immanuel Batu, the research analyzes curriculum, learning methods, industry involvement, and graduate competencies. Findings indicate SMK graduates are better prepared for employment due to intensive industrial practice, whereas The High School Double Track Program graduates exhibit greater adaptability across job sectors, including entrepreneurship. However, challenges persist: SMK struggles to keep pace with industrial advancements, while The High School Double Track Program lacks sufficient industry engagement and practical training facilities. This study underscores the need for stronger collaboration between education and industry to improve graduate employability, advocating for more adaptive education policies aligned with job market demands.